La reciprocidad superada por la equidad, el amor y la amistad - Terradas Saborit, Ignasi (ENDOXA, 2002)
The starting point of this paper is an analysis on the seminal work by Marcel Mauss L 'Essai sur le Don. A discussion of Mauss' thesis based on a comparative perspective and on historical ethnographic data bring to light a new and critical interpretation of the notions of gift, and reciprocity.